Electronic Characters and Synthesis Method of Novel Conjugated System Based on Benzodithiophene Groups - Feng, Xiantao (Mini-Reviews in Organic Chemistry, 2019)
Benzodithiophene based conjugated small molecules (SMBDTs) are usually used in organic photovoltaic (OPV), Organic Filed Effection Transistor (OFET), Organic Phototransistor (OPT) and Non-Linear Optical (NLO) chromophores. Band-gap engineering is one of the key design principles for π-conjugated materials and this can be done by altering the structures of SMBDTs with sidechain and backbone reactions. In this way, scientists develop several kinds of SMBDTs with different electron donors and acceptors. The alkoxyl and aromatic substituted BDT units are mostly used as the donors, while the alkyl cyanoacetate, dicyano, rhodamine, indenedione, thieno[3,4-c]pyrrole-4,6(5H)-dione, benzothiadiazole and diketopyrrolopyrrole groups are used as the acceptors. The electronic characters of SMBDTs including the HOMO and LUMO energy level are listed and discussed. The synthesis methods of SMBDTs are mostly in common, especially with the backbone reaction. There are about four coupling methods for the backbone reaction, mostly used is the Stille coupling methods. In this review paper, the common synthesis methods and the electronic characters by several samples are summarized to provide researchers an overview of SMBDTs’ synthesis, structures and applications.
Keywords: organic filed effection transistor